Imaging Analyses of Bone Tumors. Issue 3 (March 2020) - Errani, Costantino; Tsukamoto, Shinji; Mavrogenis, Andreas F.
Abstract : Despite the evolution in imaging, especially the introduction of advanced imaging technologies, radiographs still are the key for the initial assessment of a bone tumor. Important aspects to be considered in radiographs are the location, shape and size or volume, margins, periosteal reaction, and internal mineralization of the tumor's matrix; careful evaluation of these may provide for accurate diagnosis in >80% of cases. Computed tomography and magnetic resonance imaging are often diagnostic for lesions with typical findings such as the nidus of osteoid osteoma and bone destruction such as in Ewing sarcoma and lymphoma that may be difficult to detect with radiographs; they may also be used for surgical planning. Magnetic resonance imaging accurately determines the intraosseous extent and articular and vascular involvement by the tumor. This article summarizes the diagnostic accuracy of imaging analyses in bone tumors and emphasizes the specific radiographic findings for optimal radiographic diagnosis of the patients with these tumors.